2022
DOI: 10.1186/s13063-022-06422-6
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the ‘black box of horrendousness’: a qualitative exploration of the barriers and facilitators to conducting trials involving adults lacking capacity to consent

Abstract: Background Trials involving adults who lack capacity to consent encounter a range of ethical and methodological challenges, resulting in these populations frequently being excluded from research. Currently, there is little evidence regarding the nature and extent of these challenges, nor strategies to improve the design and conduct of such trials. This qualitative study explored researchers’ and healthcare professionals’ experiences of the barriers and facilitators to conducting trials involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…In our recent qualitative study to explore the feasibility of conducting the SWAT, research teams expressed concern about the need to seek additional consent for the SWAT in an already complex consent encounter [ 22 ]. Therefore, in the CONSULT SWAT, rather than having separate consent documents, return of the completed questionnaire by SWAT participants will be taken as an indication of their consent to participate in the SWAT.…”
Section: Methodological and Ethical Considerations For Swats Involvin...mentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent qualitative study to explore the feasibility of conducting the SWAT, research teams expressed concern about the need to seek additional consent for the SWAT in an already complex consent encounter [ 22 ]. Therefore, in the CONSULT SWAT, rather than having separate consent documents, return of the completed questionnaire by SWAT participants will be taken as an indication of their consent to participate in the SWAT.…”
Section: Methodological and Ethical Considerations For Swats Involvin...mentioning
confidence: 99%
“…Resource use will include that incurred by the team (research costs) such as time to deliver the intervention and printing/postage costs where relevant and those incurred by the proxy as SWAT participant (participant costs) such as internet use if receiving the intervention remotely. Whilst some of these costs will be similar to those encountered in SWATs and trials involving participants who provide their own consent, trials involving adults lacking capacity are more resource-intensive [ 27 ] and involve more specialised members of research teams [ 22 ]. It is therefore important to determine the cost of conducting these studies because this could have implications for the affordability and decisions about whether or not to proceed with future SWATs in these populations.…”
Section: Methodological and Ethical Considerations For Swats Involvin...mentioning
confidence: 99%
“…The need for more guidance for RECs who are reviewing emergency and urgent care trials and support for consent processes for patients and members of the public who join research teams and advise on studies, has also been highlighted [106,109,117].…”
Section: Future Researchmentioning
confidence: 99%
“…To inform the development of the CONSULT SWAT, we conducted a qualitative study (CONSULT-ENABLE) to explore researchers' and healthcare professionals' views about the acceptability and feasibility of conducting the SWAT, and how the DA might be implemented in practice. The study also explored the barriers and facilitators to conducting trials involving adults lacking capacity, the design of the qualitative study and ndings relating to this aspect have been previously reported [33]. Interviews were conducted with 26 UK researchers and healthcare professionals with experience in a range of roles, trial populations and settings.…”
Section: Establishing the Acceptability And Feasibility Of Conducting...mentioning
confidence: 99%